Assessment of cognizance and execution of biomedical waste management among health care personnel of a dental institution in Bhubaneswar - Swati Patnaik; Nupur Sharma (Wolters Kluwer Medknow Publications, 2018)
Introduction: Inadequate knowledge of handling biomedical waste (BMW) may have serious health consequences and a significant impact on the environment as well. Judicious management of waste is not only a legal necessity but also a social responsibility. However, extreme laxity in the implementation of rules coupled with inadequate training of healthcare personnel leads to indiscriminate disposal of biomedical waste. Aim: The aim of this study is to assess knowledge, attitude, and practice (KAP) regarding BMW management and to determine the correlation between KAP and professional category. Materials and Methods: A cross sectional study was conducted among 168 healthcare personnel. A predesigned and pretested structured 34 item questionnaire was used for data collection. A self made scoring system was devised to categorize KAP as good, average, and poor. Data entry and analysis was performed using SPSS version 20. To determine whether there was any correlation between KAP and professional category Spearman's rank correlation coefficient was computed. Value of P < 0.05 was considered to be statistically significant. Results: KAP were found to have a significant positive correlation (P = 0.002, 0.04, and <0.001, respectively) with the professional category. Conclusion: The need for comprehensive training programs regarding BMW management is highly recommended to all hospital staff.